Coherent Control of Single Molecules via Phase-Shaped Two-Photon Excitation at Room Temperature - Xin-peng Xu; Tobias M. Herkenrath; Ullrich Scherf; Richard Hildner (Ultrafast Science)
Coherent control has been achieved in atoms and small molecules in gas phase during the past few decades. An intriguing demonstration of coherent control is a so-called “dark pulse” that cancels 2-photon transition probabilities despite exposing the target to the full power spectrum of transform-limited laser pulses. However, for larger functional molecules in condensed phase at room temperature, ensemble measurements do typically not allow exerting full control over competing pathways due to the unavoidable influence of the surrounding (mostly complex) environment. Here, we demonstrate room-temperature coherent control exploiting a nonresonant 2-photon transition into a higher excited state of single conjugated polymer chains embedded in a disordered matrix, including proof-of-principle experiments on bulk films. To manipulate the 2-photon transition probability, we exploit complex pulse sequences, created by a systematically varied cosinusoidal spectral phase applied to the excitation laser spectrum. For single molecules, the phase-dependent response varies from molecule to molecule, which reflects the spectral heterogeneity (position, linewidth) of their 2-photon transitions. These data indicate that coherent control of single molecules requires optimization of parameters for each individual molecule. The experimental data are reproduced by a simple model that allows to directly retrieve the 2-photon absorption spectrum of each single molecule. Our coherent-control approach is a powerful and robust way to obtain spectral characteristics of higher excited states of single molecules and to manipulate the excited-state dynamics in condensed phase at room temperature. It holds the potential to be useful for the characterization of complex organic functional materials.